Avaliação dos valores de destorque do parafuso do pilar após a pré-carga com e sem superfície dlc em função do tempo (in vitro) - Brum, Ronaldo Neves (2007)
The aim of this work was to evaluate the detorque values of screws without and with surface treatment, according to different time intervals, after abutment connection to an external hexagonal implant. Twenty screws and 20 abutments (Brånemark Philosophy System) were used in this study. The screws were divided in two groups of ten each, with the experimental group receiving a diamond-like carbon (DLC) surface. All abutments were torque-tightened to the implants with 35Ncm, by means of an analog torque device (Tonichi). Then, the detorque values were measured after 2, 5, 10, 30 minutes, and 24 hours. The Friedman and the ANOVA tests for repeated measures, followed by the Tukey test (5% significant level) were applied for the groups without and with surface treatment, respectively, to identify statistically significant differences among the studied periods within each group. The results in the control and experimental groups for the proposed times were: (30.6 Ncm / 32.1Ncm), (29.9Ncm / 31.8Ncm), (29.7Ncm / 31.2Ncm), (28.8Ncm / 29.8Ncm), (26.6Ncm / 28.1Ncm). Data analysis showed statistically signficant differences among the studied periods within each group (P<0,001). It was concluded that: 1) Detorque values were higher in the experimental group for all tested periods; 2) The clinician must allow 24 hours before the final torque on the abutment screws connected to the implant.